Growth rate, Lipid and Fatty acids content in some Marine and Freshwater diatoms - Elfituri, Abdulfattah (Journal of King Abdulaziz University: Marine Sciences, 2025)
Diatoms are photosynthetic organisms that can produce lipids in large amounts within a short time. Their biomass can be processed into biofuels and other valuable commercial products. In this research, six diatom species were isolated from Malaysian water (seawater and freshwater) and grown under the same conditions to observe differences in their lipids and fatty acids composition. The results showed significant differences in total lipid contents between freshwater and marine species. Where Sellaphora pupula, Nitzschia palea, and Craticula cuspidate (Freshwater species) had a relatively constant percentage of lipid (13 to 16.1 % of dw) while Nitzschia sp, Chetoceros calcitrans, and Nitzschia sigma (marine species) had high lipid contents (>18 %). Total fatty acid content slightly varied between marine and freshwater diatoms (43.5 to 60.5). Palmitoleic acid-C16:1 (29.9 to 39.5% of TFA) and Palmitic acid-C16:0 (15.6 to 33.2% of TFA) was predominant in most of the six diatoms studied. In addition, ω-3 and ω-6 PUFA showed a high percentage in some marine and freshwater species (Nitzschia sp and C. cuspidata), which suggested both species had a good quality of polyunsaturated fatty acid and could be used as food sources in aquaculture or in other useful applications.